Multi-Modal VR for Medical Simulation - Indhumathi, C; Chen, Wenyu; Cai, Yiyu (International Journal of Virtual Reality, 2009)
Over the past three decades computer graphics and virtual reality (VR) have played a significant role in adding value to medicine for diagnosis and treatment applications. Medical simulation is increasingly used in medical training and surgical planning. This paper investigates the multi-modal VR interface for medical simulation focusing on motion tracking, stereographic visualization, voice navigation, and interactions. Applications in virtual anatomy learning, surgical training and pre-treatment planning will also be discussed.